Simulasi umur fatik rangka main landing gear menggunakan metode elemen hingga - L. A.N. Wibawa (Universitas Mataram, 2020)
The landing gear is one crucial component in an Unmanned Aerial Vehicle (UAV) aircraft construction. Landing gear serves as the main supporting component of aircraft load when landing and take off. This research aims to investigate the fatigue design life of the main landing gear on the UAV aircraft. The main landing gear frame design used Autodesk Inventor Professional 2017, while finite element analysis used Ansys Workbench software. It is subjected to a load of 1500 N with a loading fully-reserved. The prediction for fatigue life using Gerber mean stress theory. The material of the main landing gear frame is Aluminum alloy 6061. The simulation results show that the main landing gear frame has a minimum fatigue life of up to 3.5 x 107 cycles with a minimum safety factor of 1.43.